Assessment of Epidemiological and Demographic Factors of Dengue - Deepa Harichandran (Asian Journal of Medical Research, 2016)
Introduction: Aim: To assess epidemiological and demographic factors of dengue. Subjects and Methods: One hundred fifteen cases of dengue virus infection among age group 18- 56 years of either gender were enrolled in this prospective, observational study. Assessment of clinical features such as headache, retro orbital pain, myalgia, arthralgia, rash, hemorrhagic manifestations, and leucopenia was recorded. Evaluation of NS1 antigen, IgM and IgG antibodies. NS1 antigen and IgM antibodies using ELISA method and IgG antibodies was performed. Results: Out of 115 patients, males comprised 60 (52.2%) and females 55 (47.8%). Common symptoms recorded were headache in 67%, retro orbital pain in 32%, myalgia in 52%, arthralgia in 45%, rash in 74% and bleeding in 53%. A non- significant difference between clinical features were observed (P> 0.05). NS1 was identified in 45%, IgM in 20%, IgG in 3%, NS1+ IgM in 21%, NS1+ IgG in 5% and NS1+ IgM+ IgG in 6%. Conclusion: Dengue infection was quite high among males as compared to females. In maximum cases, NS1 was identified followed by NS1+ IgM.